The prevalence of iron deficiency anemia among African asylum seeking children residing in Tel Aviv - Gideon Koren; Lielle Ross; Oren Zwang; Orel Benari (BMC, 2019)
Abstract Background It has been the impression of pediatricians at the Terem Clinic for African asylum seekers in Tel Aviv that they encounter large numbers of anemic children. The objectives of this study were 1) to quantify the prevalence of anemia among African African asylum seeking children treated in the Terem Clinic for refugees in Tel Aviv; 2) to compare it to the rates among Jewish Israeli children; 3) and to correlate it with their nutritional iron intake. Overall, this effort aims at informing changes in policies and practices that will ensure healthy development of African asylum seeking children in Israel. Methods The prevalence of anemia was calculated for all toddlers and children under the age of twelve years visiting the refugee clinic and compared to the recently reported rates of anemia among urban Jewish Israeli children of similar ages; Nutritional iron intake was calculated in a subgroup by a food frequency questionnaire translated to Amharic and Tigrinya. Results Mean age of the children (SD) was 2.96 yr. (SD 2.77) and mean hemoglobin 10.88 g/dl (1.47). Out of 386 eligible children, 131(34%) were anemic, fourfold more prevalent than reported among 263 Jewish toddlers and young children of the same age group [(11%), OR 4.15(95% ci 2.67-6.43)]. In a subgroup (n = 26) investigated for amount of daily iron intake, 46.2% did not receive the recommended daily allowance for their age. Nine of them had received iron supplements. Conclusions Low hemoglobin levels are four-fold more prevalent among the African asylum seeking children. The dietary data suggest iron deficiency as a major cause, although other etiologies need to be ruled out. Because of the adverse long term impact of early anemia on child development, new policies need to be developed to ensure that refugee children develop in a healthy manner. These should include routine mandatory supplements of iron for all refugee children, in parallel to developing an educational program for parents how to achieve iron-sufficient diets for their children. Further research is needed to guide public health action for these children.